Remarks by Bruno Simma. (2017) - Simma, Bruno
Abstract : Thank you, Mr. Hirsch Ballin. I will follow your instructions, although with a slight bend, but into a neighborhood that you probably agree with. I think we all agree that multilateralism is the arena for the march from bilateralism to community interest, among other fields also with regard to the settlement of disputes and the maintenance of peace—one of the great endeavors and, partly, achievements, of civilization.